2015
DOI: 10.5487/tr.2015.31.3.255
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Heterocyclic Amines and Acrylamide in Agricultural Products with Liquid Chromatography-Tandem Mass Spectrometry

Abstract: Heterocyclic amines (HCAs) and acrylamide are unintended hazardous substances generated by heating or processing of foods and are known as carcinogenic and mutagenic agents by the animal experiments. A simple method was established for a rapid and accurate determination of 12 types of HCAs (IQ, MeIQ, Glu-P-1, Glu-P-2, MeIQx, Trp-P-1, Trp-P-2, PhIP, AαC, MeAαC, Harman and Norharman) and acrylamide in three food matrices (non-fat liquid, non-fat solid and fat solid) by isotope dilution liquid chromatography-tand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…Apart from IQ, the overall recovery of HCAs conforms well to the AOAC standards, which define an acceptable recovery range as 70% to 125% for analyte concentrations at the 10 ng/g level and 75% to 120% for analyte content at 1 ng/g level in the sample (AOAC, ). The average recoveries of IQx, MeIQx, 4,8‐DiMeIQx, and PhIP using the optimized EMR‐Lipid method in our research are also comparable to values reported in the literature for the traditional Gross methods, with a recovery rate of 28.94% to 89.3% (Gibis, ; Oz & Kaya, ; Puangsombat et al., ; Smith, Ameri, & Gadgil, ), or modified methods that range from 58.2% to 107.6% (Lee et al., ; Yan et al., ), or a QuEChERS method (PSA, C18, and MgSO 4 ) ranging from 65.41& to 117.43% (Hsiao et al., ).…”
Section: Resultssupporting
confidence: 88%
“…Apart from IQ, the overall recovery of HCAs conforms well to the AOAC standards, which define an acceptable recovery range as 70% to 125% for analyte concentrations at the 10 ng/g level and 75% to 120% for analyte content at 1 ng/g level in the sample (AOAC, ). The average recoveries of IQx, MeIQx, 4,8‐DiMeIQx, and PhIP using the optimized EMR‐Lipid method in our research are also comparable to values reported in the literature for the traditional Gross methods, with a recovery rate of 28.94% to 89.3% (Gibis, ; Oz & Kaya, ; Puangsombat et al., ; Smith, Ameri, & Gadgil, ), or modified methods that range from 58.2% to 107.6% (Lee et al., ; Yan et al., ), or a QuEChERS method (PSA, C18, and MgSO 4 ) ranging from 65.41& to 117.43% (Hsiao et al., ).…”
Section: Resultssupporting
confidence: 88%
“…For samples from the in vivo pharmacokinetic experiment, we established an HPLC–internal standard method to analyze Trp‐P‐1. The internal standard method has been used to analyze HAAs previously (Lee and others ). In this study, PhIP was selected as the internal standard due to the similar chemical structure to that of Trp‐P‐1.…”
Section: Methodsmentioning
confidence: 99%
“…At the same time, the method was also applied to other food samples (bread, roasted coffee, instant coffee, cappuccino powder, and fried potatoes), and the tested AA content was lower than the EU-set level. Additionally, because of the good separation effect, LC-MS/MS can also be applied in simultaneous detection of AA and other harmful substances in one sample, which has good application value [40,41]. Wu et al used isotope-dilution ultra-performance LC-MS/MS for simultaneous detection of 4-methylimidazole and AA in 17 commercial biscuit products [42], revealing the wide presence of 4-methylimidazole and AA in biscuit products.…”
Section: Instrumental Analysis Strategies For Aa Content In Foodsmentioning
confidence: 99%